STRATEGI, PENGEMBANGAN DAN PENERAPAN KEKAYAAN INTELEKTUAL PRODUK UMKM GERABAH BUMI JAYA DI KECAMATAN CIRUAS - sulasno Dindit; Inge Dwisvimiar; Ilma Faradilla (NIAGARA Scientific Journal, 2023)
Micro, Small and Medium Enterprises (UMKM) are one of the business fields that can develop and be consistent in the national economy. Pottery is one of the UMKM products that can play a role in economic growth. One of the famous pottery in the Banten area is in Bumi Jaya Village, Ciruas District, Serang Regency, UMKM. Pottery has not been protected by intellectual property. This study aims to determine 1). Strategy and intellectual property development of jaya bumi pottery products to improve the economy in Ciruas District, Serang Regency, 2). Application of intellectual property of Bumi Jaya Pottery UMKM products to improve the economy in Ciruas District, Serang Regency. This study uses a qualitative empirical juridical approach. The results of this study are as follows 1). Intellectual property registration process, Product marketing strategy through information and communication technology. Pottery product innovation, market share expansion, digitization, design, appropriate technology 2). The implementation is through the Intellectual Property registration process to the Directorate General of Intellectual Property.